Asset returns, the business cycle, and the labor market: A sensitivity analysis for the German economy - Burkhard Heer; Alfred Maußner (Center for Economic Studies and ifo Institute (CESifo), 2011)
We review the labor market implications of recent real-business-cycle models that successfully replicate the empirical equity premium. We document the fact that all models considered in this survey with the exception of Boldrin, Christiano, and Fisher (2001) imply a negative correlation of working hours and output that is not observed empirically, while in their model, the equity premium does not result from variation in the firm value, but from changes in the relative price of two goods. In addition, we calibrate the models with regard to characteristics from the German economy and show that the equity premium is very sensitive with regard to the utility parameters.
Keywords: G12; C63; E22; E32; 330; equity premium; production CAPM; real-business cycle; labor market statistics; Real Business Cycle; Kapitalertrag; Risikoprämie; Capital Asset Pricing Model; Beschäftigungseffekt; Konjunktur; Schätzung; Deutschland